2x+3=10-3x

Simple and best practice solution for 2x+3=10-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+3=10-3x equation:


Simplifying
2x + 3 = 10 + -3x

Reorder the terms:
3 + 2x = 10 + -3x

Solving
3 + 2x = 10 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
3 + 2x + 3x = 10 + -3x + 3x

Combine like terms: 2x + 3x = 5x
3 + 5x = 10 + -3x + 3x

Combine like terms: -3x + 3x = 0
3 + 5x = 10 + 0
3 + 5x = 10

Add '-3' to each side of the equation.
3 + -3 + 5x = 10 + -3

Combine like terms: 3 + -3 = 0
0 + 5x = 10 + -3
5x = 10 + -3

Combine like terms: 10 + -3 = 7
5x = 7

Divide each side by '5'.
x = 1.4

Simplifying
x = 1.4

See similar equations:

| 1/2X7 | | 10x-4=5x+15 | | 12-(-y-19)=12 | | 5z^2-4z^4-4=0 | | x=(5x-6)+21 | | 23X-5X^2=-24 | | 4.6=5.8-p | | -(-3-7g)-11=-9-5g | | 6x^2-73x-63=0 | | 3[x-3]+2=13-x | | 3a+7(5a+7b)-10(3+5b)=14ab+50(3+4) | | 2[3x+2(x-2)]+19=(3x+1)*2 | | 8x+3-(7+9x)=-8 | | 2(3c+2d)-2(5c-3d)= | | -(3y-1)-3y+7=2 | | 2x^3-11x^2-x+5=0 | | 3(x+2)=5(3x-2) | | y=x^4-2x^3-3x^2 | | y=80x-5x^2+2 | | 24x+x^2=-1 | | ln(x/(x-9)) | | 3x+ky=25 | | (2x+4)2=25 | | (8x-5)+1=9(x+5) | | 31x^2+5=0 | | x+-7=-6 | | [8x-5]+1=9[x+5] | | ae-yd=y*y | | (-3x-6)(x-1)=0 | | a+0+y+d+e=d(0) | | -5x(5x-5)= | | x+(-7)=-15 |

Equations solver categories